Muscle Shoals [videorecording (DVD)] - Camalier, Greg; Camalier, Greg; Badger, Stephen (Producer); Badger, Stephen (Producer); Hall, Rick, 1932-2018 (Magnolia Home Entertainment, 2014)
"Located alongside the Tennessee River, Muscle Shoals, Alabama has helped create some of the most important and resonant songs of all time. Overcoming crushing poverty and staggering tragedies, Rick Hall brought black and white together to create music for the generations. He is responsible for creating the 'Muscle Shoals sound' and the Swampers, the house band at FAME Studios that eventually left to start its own successful studio known as Muscle Shoals Sound"--Container.